Perbandingan Aktivitas Antibakteri Dekokta dan Infusa Daun Iler (Plectranthus Amboinicus (Lour.) Spreng.) terhadap Bakteri Staphylococcus Aureus dan Escherichia Coli - Siregar, Rizki Marwiyah; Kusumastuti, Melati Yulia; Gunawan, Muhammad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Infectious diseases are one of the most common types of diseases suffered by people in developing countries including Indonesia. Bacteria are one of the main causes of infectious diseases and to treat bacterial infections can be done by administering antibacterial drugs. The purpose of this study was to determine the antibacterial activity of decoction and infusion from iler leaves (Plectranthus amboinicus (Lour.) Spreng.) Against Staphylococcus aureus and Escherichia coli bacteria. This research method uses quantitative and experimental nature by making infusion and decoction from iler leaves (Plectranthus amboinicus (Lour.) Spreng.) Against Staphylococcus aureus and Escherichia coli bacteria. This research was conducted from June to August 2024. The results of the study through phytochemical screening tests showed the same group of chemical compounds in the simplicia, decoction and infusion of iler leaves containing secondary metabolite compounds including flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides. Then the antibacterial activity of iler leaves against Staphylococcus aureus and Escherichia coli bacteria with various concentrations of 10%, 20% and 30% in decoction and infusion gave the strongest results at a concentration of 30%, namely in decoction with a concentration of 30% with an average inhibition zone of 12 mm, and infusion of 15.3 mm. While the antibacterial activity of Escherichia coli in decoction with a concentration of 30% with an average inhibition zone of 10.8 mm and in infusion with a concentration of 30% with an average inhibition zone of 11.9 mm. So, the test results show that infusion has higher antibacterial activity than decoction. And in the inhibition test on both bacteria, it inhibits Staphylococcus aureus bacteria faster than Escherichia coli.